Gender equality and the effectiveness of primary education in Katosi town council, Mukono district in central Uganda - Amoding, Moreen; Mwesigwa, David (Journal of Social, Humanity, and Education, 2021)
Purpose: This study aimed to assess ways by which Gender Equality affects primary education in Mukono District Research methodology: This study is a case study that concentrates on a single institute to provide information that can be used in similar businesses to establish the effect of gender equality on primary school. A case study as the research design was preferred because it helps to measure the relationship among variables. A random sampling technique was applied in the study to produce more reliable results. Results: Results indicate that majority of pupils said that three pupils shared one text book. Also, schools only hire highly skilled teachers that a helping in the accessibility of gender equal skilled teachers that a helping in the primary education. Limitations: The study covered only one town council in one district local government and so the results may not be generalized across the country or region. Contribution: The results of this study can be useful to educationists and policy planners. Keywords: Gender, Gender equality, Primary schools, UPE